Plant Abiotic Stress Responses and Tolerance Mechanisms 2023
DOI: 10.5772/intechopen.109325
|View full text |Cite
|
Sign up to set email alerts
|

Types and Function of Phytohormone and Their Role in Stress

Abstract: Plants require sunlight, water, oxygen, and minerals to grow and flourish. Along with the external environments, plant cell functioning is regulated by chemicals and plant hormones, also known as phytohormones or plant growth regulators (PGRs). Plant hormones are chemical substances, like signalling molecules found in plants at extremely low concentrations. Hormones such as auxins, cytokinins, gibberellins, ethylene, abscisic acid, jasmonic acid; salicylic acid, brassinosteroids, and strigolactones are the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Similar reports were given by Bulya et al (2023) and Hairuddin et al (2023) in maize and medicinal plants, respectively. The weekly increase in these parameters further suggests that kinetin at higher concentrations tends to increase the growth of plantlets positively, and this corroborated the report of Vaishnav & Chowdhury (2023), who observed that in a hormone-free medium, the rate of growth was very poor. Although PGR media has been helpful in the growth of this plant, there are reports of other members of Asteraceae that developed in a medium without PGRs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar reports were given by Bulya et al (2023) and Hairuddin et al (2023) in maize and medicinal plants, respectively. The weekly increase in these parameters further suggests that kinetin at higher concentrations tends to increase the growth of plantlets positively, and this corroborated the report of Vaishnav & Chowdhury (2023), who observed that in a hormone-free medium, the rate of growth was very poor. Although PGR media has been helpful in the growth of this plant, there are reports of other members of Asteraceae that developed in a medium without PGRs.…”
Section: Resultssupporting
confidence: 88%
“…The first stage in mass propagating ragleaf is determining the proper concentration of plant growth hormones, such as kinetin, for shoot and root induction. Kinetin, a synthetic cytokinin PGR, plays a crucial role in tissue culture, mainly, in promoting cell division and induction of meristematic cells, which are the precursors of shoot formation (Xiong et al;Vaishnav & Chowdhury, 2023). In their report, Hairuddin et al (2023) reported positive roles of auxin and cytokinin in maize under in vitro micropropagation.…”
Section: Introductionmentioning
confidence: 99%
“…The second gene analyzed, a probable serine/threonine kinase, acts as a positive regulator of brassinosteroid (BR) signaling. Brassinosteroids, another class of growth-promoting regulator, regulate many aspects of plant growth and development, including cell expansion and elongation (in combination with auxin) and vascular differentiation [69][70][71][72][73]. The necessity of brassinosteroids in plant growth and development has been demonstrated by the identification of many BR-deficient dwarf mutants and subsequent BRs treating experiments [74].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most well-known phytohormones include auxins, cytokinins, gibberellins, ethylene, abscisic acid, and JA. These hormones can stimulate or inhibit growth, mediate cellular differentiation, and contribute to the plant’s response to environmental stimuli ( Vaishnav et al., 2023 ). It is the cooperation of GRNs and phytohormones that inhibits cell development and morphogenesis.…”
Section: Insights Into Grns and Phytohormonesmentioning
confidence: 99%